Proceedings of 16th International Symposium on Fusion Engineering
DOI: 10.1109/fusion.1995.534506
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion microchannels and IEC grid effects using the SIMION code

Abstract: The design of the cathode grid for a spherical inertial electrostatic confinement (IEC) fusion device is described based upon the results of SIMION, an electric field and ion trajectory program. Cathode grids of varying ra&i and geometric transparency were simulated with t h~ code. Twohmensional models of energetic ions in the IEC that were produced with SIMION show the formation of ion microchannels and the Star-mode. The SIMION results also show that smaller, less transparent grids produce smaller cores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…8) This is because the grid cathode in the IECF device produces concave electric equipotential lines (which act as a converging lens for the ions) whose shapes are due to the potential of each grid wire. These lines are more distorted with a smaller number of rings, 7) which causes an increase in the ion angular momentum (L i ). The increase in L i gives the ion microchannels a certain divergence.…”
Section: Experiments 1 Observations Of the Glow Discharge Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…8) This is because the grid cathode in the IECF device produces concave electric equipotential lines (which act as a converging lens for the ions) whose shapes are due to the potential of each grid wire. These lines are more distorted with a smaller number of rings, 7) which causes an increase in the ion angular momentum (L i ). The increase in L i gives the ion microchannels a certain divergence.…”
Section: Experiments 1 Observations Of the Glow Discharge Plasmamentioning
confidence: 99%
“…Theoretical studies have suggested that the equipotential lines of the spherical IECF device were distorted by the spacing of the grid cathode wires and current feedthrough. 7,8) Some of the ions, therefore, could not pass through the center of the sphere. In addition, mitigating the distortion of these lines by decreasing the cathode transparency did not surpass the adverse effects of the increased probability of collision with the cathode, so that the recirculation ion current was decreased by decreasing the transparency.…”
Section: Introductionmentioning
confidence: 99%
“…The graphical output of SIMION adds further insight into the phenomenon involved in microchannel formation [11]. The grid cathode produces concave equipotential surfaces in the grid opening, whose shapes are due to the potential of the individual grid wires.…”
Section: A Microchannel Formationmentioning
confidence: 99%